A Rapid Transcriptome Response Is Associated with Desiccation Resistance in Aerially-Exposed Killifish Embryos - Tingaud-Sequeira, Angèle; Lozano, Juan-José; Zapater, Cinta; Otero, David; Kube, Michael; Reinhardt, Richard; Cerdà, Joan (PLOS ONE, 2013)
Delayed hatching is a form of dormancy evolved in some amphibian and fish embryos to cope with environmental conditions transiently hostile to the survival of hatchlings or larvae. While diapause and cryptobiosis have been extensively studied in several animals, very little is known concerning the molecular mechanisms involved in the sensing and response of fish embryos to environmental cues. Embryos of the euryhaline killifish Fundulus heteroclitus advance dvelopment when exposed to air but hatching is suspended until flooding with seawater. Here, we investigated how transcriptome regulation underpins this adaptive response by examining changes in gene expression profiles of aerially incubated killifish embryos at ∼100% relative humidity, compared to embryos continuously flooded in water. The results confirm that mid-gastrula embryos are able to stimulate development in response to aerial incubation, which is accompanied by the differential expression of at least 806 distinct genes during a 24 h period. Most of these genes (∼70%) appear to be differentially expressed within 3 h of aerial exposure, suggesting a broad and rapid transcriptomic response. This response seems to include an early sensing phase, which overlaps with a tissue remodeling and activation of embryonic development phase involving many regulatory and metabolic pathways. Interestingly, we found fast (0.5–1 h) transcriptional differences in representatives of classical “stress” proteins, such as some molecular chaperones, members of signalling pathways typically involved in the transduction of sensor signals to stress response genes, and oxidative stress-related proteins, similar to that described in other animals undergoing dormancy, diapause or desiccation. To our knowledge, these data represent the first transcriptional profiling of molecular processes associated with desiccation resistance during delayed hatching in non-mammalian vertebrates. The exceptional transcriptomic plasticity observed in killifish embryos provides an important insight as to how the embryos are able to rapidly adapt to non-lethal desiccation conditions.